Mg/Ca ratio-regulated phase differentiation of microbially derived CaCO3 and its effects on Cu2+, Cd2+, and Pb2+ immobilization - Kaiming Hu; Yanyang Zhao; Yishui Han; Zuozhen Han; Ruirui Meng; Xiao Gao; Jie Li; Na Guo (Journal of Hazardous Materials, 2026)

Robust photothermal regulation in large-area smart windows enabled by bimetallic NiCo hydroxide with layered structure - Yi Gao; Xiaoting Li; Qiaodeng Ding; Pengyang Lei; Xinyi Wang; Chengyu Hu; Ruirui Ren; Jinhui Wang; Guofa Cai (Chemical Engineering Journal, 2026)

Drosophila Tet mediates the host IMD antibacterial immune defense in a catalytic activity-independent manner - Chuchu Zhang; Muhammad Abdul Rehman Saeed; Yiheng Jin; Erwen Ding; Yajie Su; Sheng Hu; Ruirui Tan; Shanming Ji (Insect Biochemistry and Molecular Biology, 2026)

Indium-doped CuSnO3 perovskite hybrids for chemiresistive CO sensing - Linyan Gu; Yangtao Qian; Yiting Liu; Miao Cheng; Tao Wei; Qianqian Liu; Ruirui Wang; Wanfei Li; Zhenxiao Fu; Haiyang Jiang; Zibo Li; Bo Liu; et al. (Chemical Engineering Journal, 2026)

Bile acid-induced TBG depletion promotes trophoblast apoptosis via local thyroxine insufficiency in intrahepatic cholestasis of pregnancy - Gaoying Wang; Wen Hu; Jianyi Gao; Rong Wang; Ting Zhang; Ruirui Dong (Molecular and Cellular Biochemistry, 2026)

Deep learning based behavioural monitoring and analysis of grazing sheep - Tianci Hu; Jinxing Li; Ruirui Yan; George Vlontzos; Wenxin Zheng; Xinwen Chen; Leifeng Guo (Biosystems Engineering, 2026)

Drosophila PcG-repressive deubiquitinase complex mediates antibacterial immune defense via transcriptional regulation of Calcineurin A1 - Umar Ali; Ruirui Tan; Sheng Hu; Sen Ding; Badar Raza; Qingshuang Cai; Shanming Ji (Insect Biochemistry and Molecular Biology, 2026)

High-molecular weight hyaluronic acid protects against colitis by remodeling microbiota and restoring barrier function - Xinwei Gao; Hao Huang; Litao Hu; Weiquan Ding; Zhiliang Hou; Ruirui Xu; Guochen Du; Zhen Kang (Carbohydrate Polymers, 2026)

Reprogramming the intrinsic capsular polysaccharide biosynthesis pathway for efficient secretory production of chondroitin in Escherichia coli Nissle 1917 - Shan Hu; Siyan Zhou; Mingming Zheng; Haibo Xiong; Guobin Yin; Fengling Yang; Ping Dong; Jian Chen; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2026)

Clonidine compromises human sperm functions - Xuchang Liu; Yanfan Cui; Ruirui Qian; Yixuan Li; Zeyu Hu; Houyang Chen; Yufeng Yuan; Tao Luo (Reproductive Toxicology, 2026)

PtRu synergistic effect facilitates hydrogenation of liquid organic hydrogen carrier in aqueous phase under ambient pressure - Shuhan Lu; Jiao He; He Jiang; Yixiao Wang; Ruirui Hu; Xiang Gong; Bin Wang; Chunhai Yi; Fusheng Yang; Tao Fang (Chemical Engineering Journal, 2026)

Ecological strategies of evergreen and deciduous woody species: including nitrogen and phosphorus allocation among organs, and element-based network - Xueqin Li; Xiaoping Chen; Yongjiao Zhou; Ruirui Fan; Peter B. Reich; Dandan Hu; Quanlin Zhong; Dongliang Cheng (Oecologia, 2025)

miR-144-3p suppression mediates Nrf2 activation induced by developmental arsenic exposure in mice - Ruirui Wu; Xin Chen; Yongqin Xia; Mengqi Cui; Sihang Hou; Yuxin Hu; Huihui Wang; Jingbo Pi; Yuanyuan Xu (Toxicology, 2025)

Novel alkali-resistant nitrogen and phosphorus removal strain I4: Performance evaluation and molecular mechanism - Xiaoxuan Fan; Jiayi Zhou; Qionghua Chen; Yuwei Feng; Ruirui Han; Guangfeng Chen; Sha Yue; Yonghao Ma; Hu Shu (Bioresource Technology, 2025)

Selective and efficient adsorption of H3BO3 from Salt Lake brine solution by ZIF-67-derived hollow cobalt sulfide - Yifan Shao; Chao Hu; Ruirui Liu; Bingxin Liu; Yongquan Zhou; Jianming Pan (Desalination, 2025)

Large electrocaloric temperature change in lead-free (Bi0.47Na0.47Ba0.06)TiO3-based ceramics via regulating non-ergodic - ergodic transition - Junwen Mei; Mei Bai; Yangfei Gao; Ruirui Kang; Xiangran Pei; Haichao Hu; Junjie Xiong; Jiantuo Zhao; Feng Li; Dezhen Xue; Zhongliang Lu; Xiaojie Lou (Chemical Engineering Journal, 2025)

Engineering Komagataella phaffii cell factories for the production of chondroitin sulfate A with high sulfation degree - Haibo Xiong; Xiaogang Yang; Weijiao Zhang; Litao Hu; Gege Liu; Guocheng Du; Jian Chen; Jianghua Li; Ruirui Xu; Zhen Kang (Chemical Engineering Journal, 2025)

Airway exposure to lithium nickel manganese cobalt oxide particles induces alterations in lung microenvironment and potential kidney and liver damage in mice - Junyi Wang; Xin Fang; Ruirui Wu; Ziyu Liu; Gang Wang; Yuxin Hu; Huihui Wang; Jingbo Pi; Yuanyuan Xu (Toxicology, 2025)

Bimetallic Bi–Sn nanoparticles in-situ anchored in carbon nanofiber as flexible self-supporting anode toward advanced magnesium ion batteries - Shaoqing Pan; Miao Cheng; Chen Ma; Huaijia Jing; Tongyu Shen; Jing Hu; Qianqian Liu; Tao Wei; Ruirui Wang; Wanfei Li; Bo Liu (Chemical Engineering Journal, 2025)

Targeting STING oligomerization with licochalcone D ameliorates STING-driven inflammatory diseases - Yinghui Zhang; Yadan Liu; Bing Jiang; Lifan Chen; Jie Hu; Buying Niu; Jie Chang; Zisheng Fan; Jingyi Zhou; Yajie Wang; Dan Teng; Ning Ma; et al. (Science China Life Sciences, 2024)

Exploring the impact of hyper-treated-quantity on the performance to access GHG emission in a full-scale A2O + MBR process: from predictions to implementation - Yongfeng Hu; Yongxiang Zhang; Ruirui Sun; Kun Wang; Qing Cai (Clean Technologies and Environmental Policy, 2024)

Fine-grained method for determining size and velocity distribution patterns of flat-fan nozzle-atomised droplets based on phase doppler interferometer - Ruirui Zhang; Peng Hu; Longlong Li; Qing Tang; Jiaxuan Yang; Jiajun Yang; Liping Chen (Computers and Electronics in Agriculture, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Lithium-ion battery remaining useful life prediction: a federated learning-based approach - Ruirui Zhong; Bingtao Hu; Yixiong Feng; Shanhe Lou; Zhaoxi Hong; Fei Wang; Guangshen Li; Jianrong Tan (Energy, Ecology and Environment, 2024)

Construction of immobilized enzyme cascades for the biosynthesis of nucleotide sugars UDP-N-acetylglucosamine and UDP-glucuronic acid - Jialian Li; Yanlai Liu; Litao Hu; Ruirui Xu; Weijiao Zhang; Shan Hu; Yang Wang; Guocheng Du; Zhen Kang (Systems Microbiology and Biomanufacturing, 2024)

Understanding the effect of plastic food packaging materials on food flavor: A critical review - Fuqing Bai; Guijie Chen; Yanan Hu; Yuexin Liu; Ruirui Yang; Junsheng Liu; Ruyan Hou; Hongfang Li; Xiaochun Wan; Huimei Cai (Trends in Food Science & Technology, 2024)

Behavior classification and spatiotemporal analysis of grazing sheep using deep learning - Zhongming Jin; Hang Shu; Tianci Hu; Chengxiang Jiang; Ruirui Yan; Jingwei Qi; Wensheng Wang; Leifeng Guo (Computers and Electronics in Agriculture, 2024)

Large room-temperature electrocaloric response achieved by tailoring the first-order orthorhombic-tetragonal phase transition in BaTiO3-based ferroelectric ceramics - Ruirui Kang; Wenjing Qiao; Junjie Xiong; Haichao Hu; Ming Wu; Feng Li; Yangfei Gao; Lixue Zhang; Yingying Zhao; Xiaojie Lou (Chemical Engineering Journal, 2024)

Dissolved Mn2+ promotes microbially-catalyzed protodolomite precipitation in brackish oxidized water - Zuozhen Han; Jie Li; Yanyang Zhao; Qingyuan Chen; Xiao Gao; Kaiming Hu; Na Guo; Xiangyu Wei; Ruirui Meng; Chenlin Zhu; Maurice E. Tucker; Chao Han (Chemical Geology, 2024)

Construction of potassium cobalt iron cyanide double-hollow nanobubble prisms for high selective adsorption of cesium - Hangyu Wang; Chao Hu; Yifa Du; Ruirui Liu; Zhong Liu; Li Han; Yongquan Zhou (Journal of Water Process Engineering, 2024)

Construction of 3D network aluminum sludge-based hydrogel beads: combination of macroization, amino functionalization, and resource utilization - Aixia Chen; Xinyuan Wang; Ruirui Hu; Xiao Wei; Luxue Lv; Tong Shen; Jinzhou Wang; Shanshan Xing; Chunbo Yuan (Environmental Science and Pollution Research, 2024)

How does grazing pressure affect feed intake and behavior of livestock in a meadow steppe in northern China and their coupling relationship - Tianqi Yu; Ruirui Yan; Chu Zhang; Sisi Chen; Zhitao Zhang; LeiFeng Guo; Tianci Hu; Chengxiang Jiang; Miao Wang; Keyu Bai; Wenneng Zhou; Lianhai Wu (Science of The Total Environment, 2024)

Eco-friendly synthesis of chemically cross-linked chitosan/cellulose nanocrystal/CMK-3 aerogel based shape-stable phase change material with enhanced energy conversion and storage - Miao Cheng; Yifan Yuan; Huaijia Jing; Jing Hu; Qianqian Liu; Tao Wei; Ruirui Wang; Wanfei Li; Bo Liu (Carbohydrate Polymers, 2024)

Using UAV-based multispectral remote sensing imagery combined with DRIS method to diagnose leaf nitrogen nutrition status in a fertigated apple orchard - Guangzhao Sun; Tiantian Hu; Shuaihong Chen; Jianxi Sun; Jun Zhang; Ruirui Ye; Shaowu Zhang; Jie Liu (Precision Agriculture, 2023)

Responses of Root Physiology and Yield of Apple Tree to Water and Nitrogen Amounts under Drip Fertigation - Shaowu Zhang; Tiantian Hu; Shuaihong Chen; Ruirui Ye; Jinghang Chen; Chenming Geng (Journal of Plant Growth Regulation, 2023)

Achieving win-win outcomes with cerium-loaded porous aluminum sludge hydrogel microspheres for enhanced phosphate removal - Aixia Chen; Luxue Lv; Ruirui Hu; Xiao Wei; Juanjuan Guan; Xin Meng (Science of The Total Environment, 2023)

Enhanced phosphate adsorption studies on several metal-modified aluminum sludge: preparation optimization, adsorption behavior, and mechanistic insight - Aixia Chen; Juanjuan Guan; Ruirui Hu; Xiao Wei; Yixuan Zhang; Luxue Lv; Xinyuan Wang; Lei Zhang; Luqian Ji (Environmental Science and Pollution Research, 2023)

Integrated miRNA-mRNA analysis reveals the dysregulation of lipid metabolism in mouse liver induced by developmental arsenic exposure - Xin Chen; Ruirui Wu; Hengchao Wu; Yuxin Hu; Huihui Wang; Jingqi Fu; Jingbo Pi; Yuanyuan Xu (Journal of Hazardous Materials, 2023)

Secondary donor-derived CD19 CAR-T therapy is safe and efficacious in acute lymphoblastic leukemia with extramedullary relapse after first autologous CAR-T therapy - Delin Kong; Tingting Yang; Jia Geng; Ruirui Jing; Qiqi Zhang; Guoqing Wei; He Huang; Yongxian Hu (Journal of Zhejiang University-SCIENCE B, 2022)

Preparation of in-situ nitrogen-doped lignin-based porous carbon and its efficient adsorption of chloramphenicol in water - Aixia Chen; Yixuan Zhang; Xiao Wei; Jiaju Pang; Ruirui Hu; Juanjuan Guan (Environmental Science and Pollution Research, 2022)

Barley yellow dwarf virus-infected wheat plant modulated selection behavior of vector aphids - Zuqing Hu; Ruirui Chai; Xin Liu; Yao Dong; Dan Su; Nicolas Desneux; Xiaoling Tan; Chen Luo (Journal of Pest Science, 2022)

Apigenin inhibits growth of melanoma by suppressing miR-512-3p and promoting the G1 phase of cell cycle involving the p27 Kip1 protein - Qun Xie; Ruirui Zhang; Dandan Liu; Jing Yang; Qiang Hu; Chao Shan; Xiaohan Li (Molecular and Cellular Biochemistry, 2022)

Effects of grazing intensity on soil nematode community structure and function in different soil layers in a meadow steppe - Fengjuan Pan; Ruirui Yan; Jinling Zhao; Linghao Li; Yanfeng Hu; Ye Jiang; Jie Shen; Neil B. McLaughlin; Dan Zhao; Xiaoping Xin (Plant and Soil, 2022)

Remote Sensing of the Coastline Variation of the Guangdong–Hongkong–Macao Greater Bay Area in the Past Four Decades - Ruirui Hu; Lijun Yao; Jing Yu; Pimao Chen; Dongliang Wang (Journal of Marine Science and Engineering, 2021)
In this study, a combination of example-based feature extraction and visual interpretation was applied to analyze the coastline variations in the Guangdong–Hong Kong–Macao Greater Bay Area (GHMGBA) from the past four decades based on the Landsat satellite remote sensing image data from 1987–2018, using ENVI and ArcGIS software. The results showed that the total length of the coastline of the GHMGBA increased in the past four decades, rising from 1291 km in 1987 to 1411 km in 2018. Among these, artificial coastline increased by 450 km, while the other coastline types decreased. The type of coastline that decreased the most was bedrock coastline, by a total of 172 km. The silty coastline disappeared, and almost all of it was converted to artificial coastline. Variations in the coastline of the GHMGBA were mainly connected to human activities and showed an overall trend of advancing towards the ocean. Dynamic monitoring of coastline variations can provide a reference for the protection of natural resources, sustainable marine development and rational planning of the coastal zone.

Response to Environmental Factors of Spawning Ground in the Pearl River Estuary, China - Dongliang Wang; Lijun Yao; Jing Yu; Pimao Chen; Ruirui Hu (Journal of Marine Science and Engineering, 2021)
Spawning grounds are important areas for fish survival and reproduction, and play a key role in the supplement of fishery resources. This study investigated environmental effects on the spatiotemporal variability of spawning ground in the Pearl River Estuary (PRE), China, using the generalized additive model (GAM), based on satellite remote sensing (sea surface temperature (SST), chlorophyll-a concentration (Chl-a), sea surface salinity (SSS), depth), and in situ observations. Results showed that 39.8% of the total variation in fish egg density was explained by these factors. Among them, the most important factor was SST, accounting for 14.3%, followed by Depth, SSS, and Chl-a, with contributions of 9.7%, 8.5%, and 7.3%, respectively. Spawning grounds in the PRE were mainly distributed in the waters with SST of 22 °C, depth of 30–50 m, SSS of 16–35 ‰, and Chl-a of 6–15 mg/m3. From spring to summer, the spawning ground moved from the outlet of the PRE to the east. The distribution of the spawning ground in the PRE was mainly affected by the Pearl River Plume (PRP), Guangdong Coastal Current (GCC), and monsoons in this area.

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Microbial functional diversity, metabolic quotient, and invertase activity of a sandy loam soil as affected by long-term application of organic amendment and mineral fertilizer - Junli Hu; Xiangui Lin; Junhua Wang; Jue Dai; Ruirui Chen; Jiabao Zhang; Ming Hung Wong (Journal of Soils and Sediments, 2011)